Age-Specific Biometric Ratios of the Posterior Fossa in Pediatric Neuroimaging: Establishing Normative Reference Values - Mirfendereski, Sam; Fesharaki, Shahin; Zadehmir, Mohadeseh (Iranian Journal of Child Neurology, 2026)
Objectives: Understanding normative biometric data of the posterior fossa is imperative to elucidate pathological alterations. Consequently, a reference for normative biometric data on posterior fossa structures in pediatric populations is essential for diagnosing cerebellar hypoplasia and other associated anomalies. However, a comprehensive set of objective, age-stratified biometric ratios for key posterior fossa structures is lacking, limiting diagnostic precision. To the best of our knowledge, only one study has evaluated the biometric data of the posterior fossa components in children. Materials & Methods: The current study is a cross-sectional study conducted among children hospitalized at Imam Hossein Children’s Hospital in Isfahan, Iran, in 2022-2023. All magnetic resonance imaging (MRI) examinations, including midline sagittal sections, performed in children ≤ 15 years of age, were included. Patients with a clinical history of posterior fossa involvement or MRI abnormalities were excluded from this study. Two-dimensional (2D) parameters, including the height of the vermian (H-V), anterior-posterior diameter of the vermis (APD-V), anterior-posterior diameter of the midbrain-pons junction (APD-MP), and anterior-posterior diameter of the midpons, were all measured. Four biometric ratios were calculated to normalize posterior fossa morphology across age groups, accounting for individual size variability and providing objective criteria. Results: Four hundred twenty patients, with a mean age of 5.79 ± 4.02 years, were investigated, of whome 222 (52.9%) were boys. All parameters, except APD-V, were significantly higher in boys than in girls. Although boys had a higher mean APD-V than girls, this difference was not statistically significant. In addition, all studied parameters had the fastest growth rates in the first year and continued to grow more slowly until the end of the 15th year. Key findings reveal a mean APD-P/APD-V ratio of 0.77 ± 0.09. The ratio was generally higher in older children, indicating that pontine growth outpaces vermian expansion during development—values near or above 1.00 may suggest pontocerebellar hypoplasia. The H-V/APD-V ratio (mean 1.72 ± 0.18) shows a dip in early childhood, particularly at 1-3 years, suggestingtransient vermian flattening. The H-V/APD-P ratio declines from 2.30 in infancy to 2.11 in adolescence, reflecting posterior fossa maturation. Meanwhile, the APD-P/APD-MP ratio remains consistently around 1.91-1.95, aligning with the expected 2:1 anatomical norm, and serving as a reliable reference across age and sex groups. Conclusion: The present study showed that all posterior fossa parameters, except APD-V, were significantly higher in boys. This study establishes normative reference values for key posterior fossa ratios. The APD-P/APD-V ratio (mean 0.77 ± 0.09) increases with age, while the H-V/APD-P ratio declines from 2.30 to 2.11. The APD-P/APD-MP ratio remains stable at 1.91, consistent with the 2:1 anatomical norm. These objective criteria provide quantifiable thresholds for detecting anomalies like pontocerebellar hypoplasia.